Integrasi Jiwa Semangat Nilai-Nilai 45 (JSN 45) Dalam Penguatan Pembelajaran Sejarah Lokal di SMA Banyuwangi - Miskawi; Akhmad Touwil Firdaus; Sri Suci Dewi Wulandari; Ahmad Sulthoni (MAN Insan Cendekia Jambi, 2025)
History education plays a crucial role in shaping national identity, historical awareness, and national character in students. One approach that can strengthen history education is the Integration of the Spirit and Values ​​of '45 (JSN 45) into local history instruction in schools. This study aims to analyze the concept, urgency, and implementation strategies of JSN 45 in strengthening local history learning for students. The approach used in this research is a literature review, reviewing various academic sources, such as journals, books, and educational policy documents relevant to the integration of JSN 45 into local history instruction. The analysis was conducted using content analysis methods to explore various concepts and practices that have been implemented in history education based on national values. The results show that the integration of JSN 45 into local history instruction contributes to strengthening students' national identity, preventing social conflict, and instilling the values ​​of unity and patriotism. Several effective implementation strategies include the use of digital media and interactive technology, project-based learning, and inquiry-based learning methods. However, several implementation challenges exist, such as the lack of integration of local history into the national curriculum, limited learning resources, and teacher readiness to apply innovative methods. Therefore, collaboration between the government, educators, and the academic community is needed to develop a more inclusive and multicultural history curriculum.